The Methodology of Linguistic and Grammatical Verification in Usulī Thought: An Analytical Study of Concepts and Applications - Al-Swesi, Ibrahim Abdullah ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2025)
This study explores a nuanced topic within the field of uṣūl al-fiqh (principles of Islamic jurisprudence), specifically aiming to uncover the methodological precision adopted by uṣūlī scholars in analyzing grammatical issues and deconstructing words and structures from semantic and interpretive perspectives. Despite the breadth of grammatical studies and the variety of their topics, certain fine-grained aspects of inquiry have not received sufficient attention, remaining overlooked or bypassed—especially those analytical dimensions that yield deeper understandings of texts and their intended meanings. The study adopts a descriptive-analytical approach and is divided into two main sections, each containing two sub-sections. The first focuses on the semantic implications of general and specific terms, as well as the formulations of commands and prohibitions. The second addresses the conditionality of rulings based on ends and actions, and how that reflects upon syntactic structures. The study reveals a clear deficiency in the integration of uṣūlī terminology within traditional grammatical research. It demonstrates that the precision practiced by uṣūlī scholars was not merely linguistic rigor, but a means to regulate legal meaning and ensure the soundness of juridical inference.